(untitled) (BIRDEM Medical Journal, 2024)
Background: Hepatolithiasis (HL) is the presence of stones in the bile ducts proximal to the confluence of the hepatic ducts. It is endemic in the Asia-Pacific region. The etiology of hepatolithiasis is not fully understood but genetic, dietary and environmental factors are thought to be contributory. Malnutrition and low socioeconomic conditions are associated with a high incidence of intrahepatic stones. This study aimed to analyze the demographic and clinicopathological factors, appraise the role of surgical management and analyse the postoperative outcomes of HL in a tertiary care centre in Bangladesh. Methods: This study was conducted in the Department of Hepato-Biliary-Pancreatic Surgery and Liver Transplant (HBPS & LT), BIRDEM General Hospital, Dhaka, Bangladesh. Retrospective data of all patients operated for HL from January 2011 to December 2022 were analyzed with regard to clinical parameters, biochemical parameters and different types of surgical management. Results: A total of 52 patients underwent surgical treatment for HL. Of the patients, 65.4% were female and 34.6% were male. Of the patients, 94.2% had abdominal pain, 57.7% had fever and 28.8% presented with jaundice. A total of 30.8% of patients had a history of previous biliary surgery. Liver atrophy was present in 38.5% of cases. Hepaticojejunostomy (HJ) alone was done in 36 (69.2%) patients, hepatic resection with bilioenteric anastomosis was done in 10 (19.2%) patients and hepatic resection with T-tube placement in common bile duct (CBD) done in 6 (11.5%) patients. Endoluminal access loop was done in 2 (3.8%) patients. On followup visits, 60% of patients were asymptomatic. There was no postoperative mortality. Conclusion: Results from present study revealed encouraging results with minimal post operative complications and no mortality. BIRDEM Med J 2024; 14(3): 137-142